Crises, labor market policy, and unemployment - Bernal-Verdugo, Lorenzo E.; Furceri, Davide; Guillaume, Dominique (IMF working paper ;, 2012)
Using a sample of 97 countries spanning the period 1980-2008, we estimate that financial crises have a large negative impact on unemployment in the short term, but that this effect rapidly disappears in the medium term in countries with flexible labor market institutions, whereas the impact of financial crises is less pronounced but more persistent in countries with more rigid labor market institutions. These effects are even larger for youth unemployment in the short term and long-term unemployment in the medium term. Conversely, large upfront, or gradual but significant, comprehensive labor market policies have a positive impact on unemployment, albeit only in the medium term.